FUNGSI SOSIAL PAMBAOKAN BAKO DALAM UPACARA PERKAWINAN (Studi Kasus di Nagari Koto Beringin Kecamatan Tiumang Kabupaten Dharmasraya) - Rahma, Novita - (Pendidikan Sosiologi, 2014)
The social function of marriage ceremonias pambaokan bako in the country districts Koto Beringin Tiumang Dharmasraya, skripsi education courses sociology STKIP PGRI west Sumatera 2014. In the study the structural fungsinal by Robert K Merton. This study uses a qualitative approach and the type of research decriptif. The result of this research indicate 1. Pambaokan tradisional bako, pambaokan bako, 2. Stages in uacara marriage, consultation fees, purchases of goods, 3. Barang pambaokan bako tobacco in pambaokan bako bring in the equipment room, the equipment room, kitchenwere, 4. Pambaokan bako by the social status of bako in the form of economic pambaokan upscale, smoke in the form of economic pambaokan bako underclass, 5. The social function psmbaokan bako is manifest function, latent function, and disfungsi in pambaokan, bako in the merriage ceremony in the country Koto Beringin district Tiumang Dhamasraya.